1995
DOI: 10.1136/thx.50.1.50
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a spacer on pulmonary aerosol deposition from a jet nebuliser during mechanical ventilation.

Abstract: Background -Several factors have been identified which improve nebulised aerosol delivery in vitro. One of these is the addition ofa spacer to the ventilator circuit which improves aerosol delivery from a jet nebuliser to a model lung by approximately 30%. The current study was designed to demonstrate whether similar improvements could be demonstrated in vivo. Methods -Ten patients (seven men) were studied during mechanical ventilation (Siemens Servo 900C) after open heart surgery. Aerosol was delivered using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
35
1
4

Year Published

2001
2001
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(42 citation statements)
references
References 9 publications
2
35
1
4
Order By: Relevance
“…[7][8][9][10]12,[13][14][15][16]23 This is consistent with the dose efficiency we obtained with each device and airway used in this study, which ranged from 3 to 15%. Aerosol was generated by a pMDI and jet nebulizer placed proximal to the airway in the inspiratory limb of a heated humidified ventilator circuit attached to the artificial airway placed orally or tracheally in an adult teaching mannikin.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…[7][8][9][10]12,[13][14][15][16]23 This is consistent with the dose efficiency we obtained with each device and airway used in this study, which ranged from 3 to 15%. Aerosol was generated by a pMDI and jet nebulizer placed proximal to the airway in the inspiratory limb of a heated humidified ventilator circuit attached to the artificial airway placed orally or tracheally in an adult teaching mannikin.…”
Section: Discussionsupporting
confidence: 75%
“…Because the primary focus of previous research on aerosol delivery during mechanical ventilation was the ETT, [6][7][8][9][10][11][12][13][14][15][16] there are limited data in the literature on the delivery of inhaled medications administered with different aerosol devices in mechanically ventilated patients with TTs. Consequently, the difference between TTs and ETTs in drug delivery to ventilator-dependent patients is not clear, and determining the most efficient aerosol device for critically ill patients with a tracheostomy is essential to optimize effectiveness of drug delivery to this patient population.…”
Section: Introductionmentioning
confidence: 99%
“…Later, Fuller et al 29 confirmed that the efficiency of aerosol delivery with both pMDIs and nebulizers was lower in ventilator-dependent subjects than in ambulatory subjects. However, the delivery efficiency of aerosol devices in critical care has significantly improved over the years due to greater understanding of the scientific basis of aerosol therapy in 14,18,19,32,34,[38][39][40][41][42] There are significant differences in the delivery efficiency of aerosol devices due to many factors, which can be divided into 6 categories: (1) effect of particle size, (2) effect of drug formulations, (3) factors affecting aerosol device performance, (4) factors affecting aerosol drug delivery to ventilator-dependent patients, (5) factors affecting aerosol delivery to spontaneously breathing patients with artificial airways, and (6) effect of disease state and severity.…”
Section: Delivery Efficiency Of Aerosol Devices In Pulmonarymentioning
confidence: 99%
“…However, some of the same adjustments and limitations described for pMDIs apply equally for all nebulizers. For example, proximal placement of a nebulizer in relation to the circuit Y-piece-adapter, 47 along with incorporation of an aerosol reservoir, 48 increases drug delivery to the patient. Heated, humidified gases also have a negative impact, accounting for substantial reductions in drug delivery.…”
Section: Nebulizersmentioning
confidence: 99%